Use of a Two-Gene Methylated DNA Biomarker Assay and Nonendoscopic Balloon for Detection of Barrett Esophagus Among High-Risk Individuals in a Screening Population - Shaheen, Nicholas J.; Othman, Mohamed O.; Taunk, Jawar; Chang, Kenneth J.; Jaganmohan, Sathya; Yachimski, Patrick S.; Fang, John C.; Spataro, Joseph S.; Verma, Suman; Lee, Victoria T.; deGuzman, Brian J.; Aklog, Lishan (The American journal of gastroenterology, 2025)
INTRODUCTION:Barrett esophagus (BE) is the precursor to esophageal adenocarcinoma (EAC). We aimed to assess performance, safety, and tolerability of the EsoGuard (EG) assay on samples collected nonendoscopically with the EsoCheck (EC) device (EG/EC) for BE detection in the intended-use population meeting American College of Gastroenterology guideline criteria (chronic gastroesophageal reflux disease and 3+ additional risk factors).METHODS:We performed a prospective, multicenter study (NCT04293458) to assess EG performance (primary endpoint) on cells collected with EC, for detection of BE and EAC using esophagogastroduodenoscopy (EGD) and biopsies as the comparator. Twenty-four sites across the United States and Spain participated. EC safety and usability were assessed as secondary endpoints.RESULTS:180 male subjects aged >50 years with chronic gastroesophageal reflux disease met eligibility criteria, of which 163 (90.6%) had EGD and successful EC administration. Mean age was 60.5 years, 34.4% were obese, 56.7% had tobacco history, and 3.9% had a 1st degree relative with BE or EAC. Of 122 samples analyzed, 93 contributed to the primary endpoint analysis. Eight subjects (8.6%) in the Primary Analysis Population had BE on EGD, none with dysplasia. Sensitivity of EG for BE was 87.5% (95% confidence interval [CI] 47.4-99.7), specificity was 81.2% (95% CI 71.2-88.8), positive predictive value was 30.4% (95% CI 13.2-52.9), and negative predictive value was 98.6% (95% CI 92.3-99.96). Mild esophageal abrasions were observed in 1.5%; no serious adverse events were reported.DISCUSSION:This study in the intended-use population suggests that EG/EC is promising for BE screening. While future work is necessary to define its performance characteristics with more precision, this approach may provide a safe, accurate, and well-tolerated nonendoscopic alternative in high-risk patients.